Perlindungan Hak Atas Pendidikan Bagi Masyarakat Adat Terpencil Dari Perspektif Undang-Undang No. 20 Tahun 2003 Tentang Sistem Pendidikan Nasional Di Dusun Rengga Desa N’toke Kecamatan Wera Kabupaten Bima - Kafrawi - (Fakultas Hukum Universitas Mataram, 2011)
The Protection of the Right to Education for the Isolated Adat Community under Perspective of the Act Number 20 Year 2003 on the National Education System In Rengga Campong, N’toke Village, Wera District, Bima Regency is the title of this research. The Rengga Compong located in N’toke Village, Wera District, Bima Regency qualifies to be a territory of the Isolated Adat Community under the Decision of Republik Indonesia Predsiden Number 111 Year 1999. This research is intended to know the application of the policy of Local Government of Bima Regency in giving services of Basic Education basic for the isolated comminities and to know the handycap faced by the Local Government of Bima Regency in giving these services. In collecting field data, this research uses participated method conducted through three stages, namely the stages: (1) of the location mapping and plumbing areal; and (b) of the decent study. Its results are: (a) the Local Government of Bima Regency has taken policy in the field of Basic Education basic for the isolated comminities but it implementation is not maximal yet; and (2) the execution of physical development is the handycap by the Local Government of Bima Regency since to reach this Campong is difficult so the cost is very expensive.